Adaptasi Muskuloskeletal Atlet Asli NTT: Perspektif Biomekanik - Louk, Michael Johannes Hadiwijaya; Runesi, Salmon; Utomo, Andy Widhiya Bayu; Siagian, Fera Ratna Dewi; Neolaka, Erwin Sarnoto (Jurnal Porkes, 2025)
This study aims to examine the musculoskeletal adaptations of indigenous athletes from East Nusa Tenggara (NTT) from a biomechanical perspective. NTT athletes exhibit unique biomechanical characteristics influenced by environmental factors and habitual physical activity from an early age. This study employs a quantitative approach using experimental biomechanics analysis. The research subjects consist of local NTT athletes compared to national athletes in various biomechanical parameters, including bone mineral density (BMD) and ground reaction force (GRF). The results indicate that NTT athletes have higher BMD, particularly in the tibia and femur, demonstrating structural adaptations to repetitive mechanical loading. Additionally, the vertical GRF of NTT athletes is lower during the landing phase, suggesting a more efficient biomechanical strategy for impact absorption. These adaptations contribute to enhanced performance and physical endurance. This study provides new insights into sports biomechanics and can be utilized to design more tailored training programs for athletes in similar regions.